2020
DOI: 10.3390/ma13030552
|View full text |Cite
|
Sign up to set email alerts
|

Formation Mechanism of Dilute Region and Microstructure Evolution in Laser Solid Forming TA15/Ti2AlNb Dual Alloy

Abstract: TA15/Ti2AlNb multiple-layer samples and a dual-alloy sample were fabricated by laser solid forming (LSF) in this study. The formation mechanism of the dilute region and microstructure evolution of the dual alloy were analyzed. The results confirmed a “step” distribution of the composition among several initial layers in the multiple-layer samples, which can be explained by calculating the ratio of the remelted zone to the deposited Ti2AlNb zone in each deposited layer. However, the “step” compositional distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The composition transition layer added between the two alloys improves the compositional continuity, and the composition distribution of the gradient titanium alloy with composition transition layer was displayed in figure 9. It can be noticed that the content of the main alloy elements, Ti, Al and Nb, are distributed continuously and showed a nearly linear change as a result of sufficient diffusion between the layers [18]. The element of Sn is stepwise decreased, but not obvious because of the low content, which was also found in previous studies about TA15 (near-α titanium alloy)-Ti2AlNb FGMs by Chen et al [19,20].…”
Section: The Composition Differences Of Gradient Titanium Alloy With ...supporting
confidence: 70%
See 1 more Smart Citation
“…The composition transition layer added between the two alloys improves the compositional continuity, and the composition distribution of the gradient titanium alloy with composition transition layer was displayed in figure 9. It can be noticed that the content of the main alloy elements, Ti, Al and Nb, are distributed continuously and showed a nearly linear change as a result of sufficient diffusion between the layers [18]. The element of Sn is stepwise decreased, but not obvious because of the low content, which was also found in previous studies about TA15 (near-α titanium alloy)-Ti2AlNb FGMs by Chen et al [19,20].…”
Section: The Composition Differences Of Gradient Titanium Alloy With ...supporting
confidence: 70%
“…Wu et al [6] prepared γ-TiAl/Ti2AlNb dual alloy without cracks by direct metal deposition, and discovered that a transition zone with gradual change of compositions and microstructures was generated between γ-TiAl and Ti2AlNb alloy and an obvious boundary was observed between layers of the transition zone. Tan et al [7] fabricated TA15/Ti2AlNb dual alloy by laser solid forming, and found that the compositional variation tends to be continuous and smooth while the micro-hardness exhibits discontinuous characteristics. Thus, directly connecting two metals by laser deposition may result in discontinuous properties due to differences in composition and thermophysical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Vacuum diffusion bonding using a Ti interlayer allowed for the achievement of sufficient joint strength [ 17 ]; however, this method imposes considerable limitations in terms of component geometrical complexity. The laser metal deposition AM process using TA15 and Ti 2 AlNb alloy powders was used to prepare bimetallic samples [ 18 ]. While this method has great potential in the fabrication of bimetallic titanium alloy/titanium aluminide structures, it offers substantially less possibilities in terms of complex geometrical features and worse accuracy compared to powder-bed fusion AM techniques.…”
Section: Introductionmentioning
confidence: 99%